(untitled) (Eurasian Journal of History, Geography and Economics, 2023)
There are wide opportunities for the development of this industry in Uzbekistan, strengthening the preservation of the unique cultural heritage that reflects the rich history and culture of the nation, digitization of the industry, innovative development and strengthening of the material and technical base, effective application of world best practices. is one of the most important factors of socio-economic development of regions